ORGANISASI PAPUA MERDEKA SEBAGAI ORGANISASI TERORIS BERDASARKAN UNDANG-UNDANG NO 5 TAHUN 2018 - Nafa Afrillia; Ferry Edward (Faculty of Law, Universitas Trisakti, 2023)
The Free Papua group (OPM) was declared a terrorist group in accordance with Law Number 5 of 2018. OPM, on the other hand, is seen as a group of freedom fighters. Problem formulation: Is the Free Papua group (OPM) determined to be a terrorist group in accordance with Law No. 5 of 2018 and what are the legal repercussions of the Free Papua Organization (OPM)'s creation as a terrorist organization? The research method used is normative legal research and is analytically descriptive in nature, the data is processed qualitatively and conclusions are drawn using deductive logic. As for the research results, discussion and conclusions in the study; based on Article 1 number (3) in conjunction with Article 6 of Law no. 5 of 2018 concerning the Eradication of Acts of Terrorism, the government's designation of OPM as a terrorist organization is in accordance with applicable regulations. The legal consequences of the designation of OPM as a terrorist organization, the act of terrorism is a Criminal Act of Terrorism as stipulated in Article 5 of Law Number 5 of 2018.